Effect of a visual tracking intervention on attention and behavior of attention deficit hyper activity children - Shiva Janmohammadi; Hojjat Allah Haghgoo; Mojgan Farahbod; Paul G. Overton; Ebrahim Pishyareh (Bern Open Publishing, 2020)
Attention deficit hyperactivity disorder is characterized by several cognitive and behavioral problems such as inattention and impulsivity, abnormal control of eye movements and relocation, visual fixation and visuospatial perception. There is a link between core motor functions such as oculomotor function and cognition to the extent that the oculomotor system acts as a mediator between the motor and cognitive functions. Therefore, the effects of eye-tracking intervention were investigated on attention in these children. Thirty - nine boys with ADHD, 6 to 10 years of age were recruited and randomized to receive current occupational therapy (control group), or occupational therapy accompanied with eye-tracking exercises (experimental group). They were evaluated using the Conner's Parent Rating Scale, the Continuous Performance Task-2, and the Test of Visual-Motor Skills-Revised before and after the intervention. Significant improvements in the mean scores of cognitive problems (F=9/22), coping behavior (F=6.03) and hyperactivity (F=9.77) were detected in the posttest between the two groups (p<0.05). Furthermore, in the Continuous Performance Test scores, detectability (F=5.68), omission errors (F=17.89), commission errors (F=19.45), reaction time (F=8.95), variability (F=7.07), and preservation (F=6.33) showed significant differences between control and experimental groups (p<0.01). It appears that eye-tracking interventions designed based on the isolation of neck and eye movement might have an important role in improving cognitive function and coping behaviors in these children. It seems that these exercises could increase eye movement control; improve cognitive function and response inhibition.